2015
DOI: 10.1007/s00540-015-1974-3
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management and outcome of patients with Rett syndrome undergoing scoliosis surgery: a retrospective review

Abstract: Our case series demonstrates a high incidence of complications in this subpopulation, mainly postoperative. Extreme postoperative vigilance is required and recovery in a high dependency unit is highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Similarly, as many as 40% of people with Rett syndrome have been reported to undergo corrective spinal surgery (Anderson, Wong, Jacoby, Downs, & Leonard, ) and children with Rett syndrome are very likely to undergo spinal fusion (Karmaniolou et al., ). Whilst positive outcomes of spinal surgery have been reported (Downs et al., ; Kerr et al., ; Larsson et al., ), it is associated with a high rate of post‐operative major medical complications (Gabos, Inan, Thacker, & Borkhu, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, as many as 40% of people with Rett syndrome have been reported to undergo corrective spinal surgery (Anderson, Wong, Jacoby, Downs, & Leonard, ) and children with Rett syndrome are very likely to undergo spinal fusion (Karmaniolou et al., ). Whilst positive outcomes of spinal surgery have been reported (Downs et al., ; Kerr et al., ; Larsson et al., ), it is associated with a high rate of post‐operative major medical complications (Gabos, Inan, Thacker, & Borkhu, ).…”
Section: Discussionmentioning
confidence: 99%
“…<25%; Cans et al, 1999) of those with intellectual disabilities requiring postural care will have cerebral palsy. Indeed, a number of specific conditions related to intellectual disabilities may result in the need for postural care (Ager et al, 2006;Burns, Powell, Hsia, & Reinker, 2003;Butler et al, 2002;Damasceno, Cristante, Marcon, & Barros Filho, 2014;Detweiler, Thacker, Hopkins, Conway, & Gripp, 2013;Imagama et al, 2013;Karmaniolou, Krishnan, Galtrey, Cleland, & Vijayaraghavan, 2015;Kerr, Webb, Prescott, & Milne, 2003;Laurier et al, 2015;Li, Shen, Liang, & Sheng, 2015;de Lind van Wijngaarden, de Klerk, Festen, & Hokken-Koelega, 2008;Takebayashi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In their postoperative study of Rett syndrome, Karmaniolou et al . did not detect differences in postoperative pain management of girls with Rett syndrome undergoing scoliosis surgery when comparing the experiences of 24 girls to existing pediatric postoperative guidelines. While this is an encouraging finding, the current sample, although smaller, used matched control groups (developmentally typical and developmentally disabled) on age, gender, and surgical procedure—perhaps increasing the ability to detect differences specific to the surgical procedure and its postoperative analgesic management.…”
Section: Discussionmentioning
confidence: 85%
“…The purpose of the current study was to further compare postoperative pain assessment scores and management practices in girls with Rett syndrome and extend the Karmaniolou et al . study by comparing a Rett syndrome sample against age‐ and gender‐matched controls across the same surgical procedure. Because previous studies have shown a discrepancy in pain management based on cognitive impairment associated with developmental delay , two comparison groups were included in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation